High-resolution electrohydrodynamic jet printing of small-molecule organic light-emitting diodes. Issue 32 (27th July 2015) - Kim, Kukjoo; Kim, Gyeomuk; Lee, Bo Ram; Ji, Sangyoon; Kim, So-Yun; An, Byeong Wan; Song, Myoung Hoon; Park, Jang-Ung
Abstract : An electrohydrodynamic jet (e-jet) printed high-resolution (pixel width of 5 μm) small-molecule organic light-emitting diode (OLED) is demonstrated. Abstract : The development of alternative organic light-emitting diode (OLED) fabrication technologies for high-definition and low-cost displays is an important research topic as conventional fine metal mask-assisted vacuum evaporation has reached its limit to reduce pixel sizes and manufacturing costs. Here, we report an electrohydrodynamic jet (e-jet) printing method to fabricate small-molecule OLED pixels with high resolution (pixel width of 5 μm), which significantly exceeds the resolutions of conventional inkjet or commercial OLED display pixels. In addition, we print small-molecule emitting materials which provide a significant advantage in terms of device efficiency and lifetime compared to those with polymers.